From sex work to refuge: life story of a Salvadoran trans activist woman - Arévalo, Amaral (2020)
This paper analyzes the relationship between the Maras, the forced displacement, and the refuge of Salvadoran lesbian, gay, bisexual, trans, intersex and other sexual and gender identities (LGBTI+) through the illustrative case of Karla Avelar. The Maras’ actions such as extortion, threat, persecution or murder led to forced mobility as a means of escape and untimely flight from the country. The refuge becomes, in many cases, the only chance to survive for Salvadoran LGBTI+ people escaping from the siege of the Maras.